1986
DOI: 10.1128/aac.29.4.654
|View full text |Cite
|
Sign up to set email alerts
|

Hospital distribution, persistence, and reintroduction of related gentamicin R plasmids

Abstract: A single plasmid clone was predominantly responsible for gentamicin resistance at the Minneapolis Veterans Administration Medical Center (MVAMC) for 9 years, although two unrelated R plasmids were found.Epidemiological data and restriction endonuclease analysis of 25 plasmid isolates suggested that the clonally derived plasmid population had persisted at the hospital. However, one case of reintroduction of the original epidemic plasmid from a hospital in another state was documented 4 years after the introduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

1986
1986
1991
1991

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Molecular studies showed that the gentamicin resistance determinant was located on a transposon that had jumped into various plasmids in K. pneumoniae. Many other examples have been reported (47,58,110,111,144,167,195), including those occurring in Staphylococcus aureus (115,127).…”
Section: History Of Plasmid Profiles In Three Examplesmentioning
confidence: 99%
“…Molecular studies showed that the gentamicin resistance determinant was located on a transposon that had jumped into various plasmids in K. pneumoniae. Many other examples have been reported (47,58,110,111,144,167,195), including those occurring in Staphylococcus aureus (115,127).…”
Section: History Of Plasmid Profiles In Three Examplesmentioning
confidence: 99%
“…Some have carried the 2"-adenyltransferase determinant and have been isolated since the 1970s in many parts of the world (7). Other R plasmids, although relatively stable, have been shown to evolve with time under natural conditions within medical centers (2,3,10). The recent discovery of a novel betalactamase gene, which so far appears to be limited to Ohio, gave us the opportunity to study a geographically welldefined set of R plasmids.…”
mentioning
confidence: 99%
“…Many of these resistant organisms were shown to carry resistance or R plasmids that bore the genetic information for enzymatic resistance and that could be transferred from organism to organism (6,10,11,18). An outbreak of this type was initially noted at our institution in 1975, first among Klebsiella species, then among Serratia species, and eventually among multiple other members of the family Enterobacteriaceae (4,18).…”
mentioning
confidence: 99%